Do mar à mesa: a pesca e a alimentação em Arraial do Cabo entre as décadas de 1930 e 1960 - Brettas, Luiz Fernando de Melo (2018)
From a fishing village dedicated almost exclusively to fishing to the seat of a large chemical industry of national interest: since the creation of the Companhia Nacional de Álcalis (National Company of Alkalis) by decree, in 1943, until the effective beginning of its operations in 1960, Arraial do Cabo lived a process of economic and social transformation that aroused the interest of researchers and research institutions that sought to know more about the habits and customs of the local population, who had fishing as their main economic source and as the center of the social life of their residents. The present work seeks to analyze the research carried out in Arraial do Cabo during the decades of 1930 to 1960 and to understand the dynamics of the process of artisanal fishing - from the sea - and salting of fish practiced in Arraial do Cabo, in order to know the products used in the food of its inhabitants and to record the recipes and ways of preparing - at the table - the fish and other foods consumed by the population between those decades. Among the subjects of these narratives are fishermen, fish merchants, women salt processors and witnesses of this period who shared their stories and memories during the interviews conducted to carry out this work